Insight of pancreatic cancer: recommendations for improving its therapeutic efficacy in the next decade - Zhi-Hang Xu; Wen-Quan Wang; Wen-Hui Lou; Liang Liu (Journal of Pancreatology, 2022)
Pancreatic cancer is one of the most malignant digestive system tumors. The effectiveness of pancreatic cancer treatment is still dismal, and the 5-year survival rate is only about 10%. Further improving the diagnosis and treatment of pancreatic cancer is the top priority of oncology research and clinical practice. Based on the existing clinical and scientific research experience, the review provides insight into the hotspots and future directions for pancreatic cancer, which focuses on early detection, early diagnosis, molecular typing and precise treatment, new drug development and regimen combination, immunotherapy, database development, model establishment, surgical technology and strategy change, as well as innovation of traditional Chinese medicine and breakthrough of treatment concept.